Examining Pregnancy Related Socio-Cultural Factors Among Adolescent Girls in the Komenda-Edina-Eguafo-Abrem Municipality in the Central Region of Ghana: A Case-Control Study - Ahinkorah, Bright Opoku; Hagan Jr., John Elvis; Seidu, Abdul-Aziz; Mintah, Joseph Kwame; Sambah, Francis; Schack, Thomas; Hormenu, Thomas (Frontiers in Public Health, 2019)
This study sought to examine the socio-cultural factors associated with pregnancy among adolescent girls in KEEA Municipality in the Central Region of Ghana. Using a case-control design, a facility-based sampling approach was used to select 400 adolescent females aged between 15-19 years. Chi-square analyses on the strictness level of rules and regulations in family (χ2 [1] = 62.010, p< 0.05), freedom within the family to discuss issues related to sexuality (χ2 [1] = 9.600, p< 0.05), religious support of sex before marriage (χ2 [1] = 4.312, p< 0.05), peer influence to engage in sexual intercourse χ2 [1] = 7.793, p<0.05), reaction of parents towards pregnancy (χ2 [1] = 70.064, p< 0.05), and reaction of siblings toward pregnancy (χ2 [1] = 66.702, p< 0.05) were significantly related to adolescents’ pregnancy status. Additionally, binary logistic regression analysis also showed that non-pregnant adolescents were 7 times more likely to belong to families with strict rules and regulations compared to pregnant adolescents (OR = 0.14, 95% CI = [0.07 – 0.25], p ≤ 0.01). Non-pregnant adolescents were 3 times more likely to have freedom within the family to discuss issues related to sexuality compared to pregnant adolescents (OR = 0.33, 95% CI = [0.18 –0.59], p ≤ 0.01). However, pregnant adolescents were 3 times more likely to be influenced by their peers to engage in sexual intercourse (OR = 2.63, 95% CI = [1.46 – 4.74], p ≤ 0.001) and 3 times more likely to have parents with positive reaction towards adolescent pregnancy compared to non-pregnant adolescents (OR = 2.97, 95% CI = [1.15 – 7.70], p ≤ 0.05). Additionally, these pregnant adolescents were 8 times more likely to have siblings with positive reaction towards adolescent pregnancy (OR = 7.74, 95% CI = [2.59 – 21.4], p ≤ 0.001) compared to their non-pregnant counterparts. Specific strategies need to involve multifaceted interventions that include education, competency-based skill training and support for young people, especially pregnant adolescents. Further research ought to determine which other factors would help us better understand circumstances that may lead to adolescent pregnancies in other areas of the region.